2015
DOI: 10.1097/mat.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Left Ventricular Assist Device Through an Axillary Access is a Promising Approach to Improve Outcomes in Refractory Cardiogenic Shock Patients

Abstract: Cardiogenic shock (CS) causes significant morbidity and mortality and such patients can deteriorate rapidly. Temporary left ventricular assist devices (LVADs) are a promising approach to manage these patients. The following is a case series in which patients stabilized with a temporary LVAD for CS improvement were analyzed retrospectively. Between June 2011 and January 2014, 15 patients received temporary devices through an axillary approach (mean age: 53 ± 15, 93% male). Mean survival time was 317.8 ± 359.5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…In total, 74 studies were screened for eligibility, and 22 studies met inclusion criteria and were included in the final analysis. 1,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
Section: Search Resultsmentioning
confidence: 99%
“…In total, 74 studies were screened for eligibility, and 22 studies met inclusion criteria and were included in the final analysis. 1,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
Section: Search Resultsmentioning
confidence: 99%
“…Multiple studies have shown that deployment of the Impella via the axillary or subclavian artery approach is safe and feasible. [3][4][5] No studies thus far have evaluated the benefits of early mobility in patients implanted with the Impella device on short-or long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the left-sided support options, the Impella 2.5 LP and CP devices can be deployed percutaneously, while the Impella 5.0 device requires surgical vascular access through a conduit graft and is commonly deployed via the axillary artery. [2][3][4] Recent reports support the use of axillary intra-aortic balloon pump (IABP) for hemodynamic support; 5 however, no studies have reported on the clinical utility of axillary deployment of an Impella 5.0 pump. The purpose of our study was to evaluate mobility levels among patients with CS being treated with an axillary Impella 5.0 pump.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a retrospective review of 228 patients who had ventricular assist device‐Impella insertion from January 2014 to December 2015 at Detroit Medical Center, Michigan, USA. All patients had two sequentially placed 6 Fr Perclose‐ProGlide closure devices Preclosed (“Preclose” technique) at 90° angle prior to placing a 13‐14 Fr arterial sheath for Impella.…”
Section: Methodsmentioning
confidence: 99%